Analisis Hukum Tanggung Jawab Direksi atas Tindakan Ultra Vires pada Perseroan Perorangan Berdasarkan Undang-Undang Cipta Kerja dan Undang-Undang Perseroan Terbatas - Nouval Rivaldi Putra (Jurnal Hukum Lex Generalis, 2025)
A limited liability company (PT) as a legal entity has the principle of limited liability. Through the Job Creation Law, the concept of a sole proprietorship has emerged, allowing one person to establish a PT. However, the principle of separation of liability and the potential for ultra vires actions pose legal challenges for the directors' accountability. The purpose of this study is to examine the application of the ultra vires principle in determining director liability in a sole proprietorship and the legal implications for the personal liability of directors in a sole proprietorship that engages in ultra vires actions under the Limited Liability Company Law and the Job Creation Law. The research method used is normative legal analysis with descriptive analytical techniques. The ultra vires principle in sole proprietorship companies, although not explicitly regulated, applies through the interpretation of the authority of the board of directors based on the Limited Liability Company Law and the Job Creation Law. The board of directors, who are also the sole shareholders, are required to act in accordance with the articles of association and the law. Actions exceeding their authority are classified as ultra vires, invalid, and not binding on the company, thereby shifting liability to the individual. As a result, the principle of limited liability is nullified, becoming unlimited liability through the doctrine of piercing the corporate veil, with liability for losses and potential criminal penalties if accompanied by bad faith or gross negligence.